7-week aerobic exercise training reduces adipocyte area and improves insulin sensitivity in Wistar rats fed a highly palatable diet - Garcia, Nádia F. [UNESP]; Silva, Carmem P. Valgas Da [UNESP]; Ferreira, Maycon Jr. [UNESP]; Oharomari, Leandro K. [UNESP]; Rocha, Thalita; Moraes, Camila De (Universidade Estadual Paulista, 2016)
The aim of this study was to evaluate the effect aerobic exercise training on fat pad mass, adipocyte size, leptin release and insulin sensitivity in rats fed with high fat-palatable diet. Twenty-four male Wistar rats (250-260g) were divided into four groups: sedentary control (CTR/SD), trained control (CTR/TR), obese sedentary (OB/SD) and obese trained (OB/TR). Obese groups were fed with high fat-palatable diet (27% of fat) and control groups fed with AIN-93. Our results showed that aerobic exercise training was effective to reduce body weight and epididymal fat mass in CTR/TR and OB/TR. Insulin and glucose levels were increased in OB/TR compared with OB/SD. Aerobic exercise training reduced the average area of adipocytes in CTR/TR and OB/TR and it was associated with reduced plasma insulin and leptin. In conclusion, 7-week aerobic exercise training reduces adipocyte area and improves insulin sensitivity and leptin levels in high fat-palatable diet-fed Wistar rats.
Keywords: aerobic exercise training; high fat diet; insulin; leptin